BAKTI SOSIAL PEMERIKSAAN STATUS NUTRISI PADA ANAK DI BANJAR JAGATAMU, DESA MELILING, TABANAN - I Gusti Ayu Prema Yani Sidemen; Ida Ayu Mirah Agung; I Made Benni Labba P. (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Malnutrition in children under 5 years of age is still one of the leading health problems in Indonesia. Early detection of malnutrition in children is vital to allow early intervention. Unfortunately, parents' awareness of the importance of routine nutritional status assessments of their children is still low. Thus, malnutrition in children tends to be recognized late and leads to stunting. The Community Service Team from the Faculty of Medicine, Mahasaraswati University, Denpasar, conducted a nutritional status assessment for children in Banjar Jagatamu aiming at detecting malnutrition in children as well as increasing parental awareness of the importance of routine nutritional status assessment for their children. In total, 27 children aged 0-5 years underwent height, weight, and head circumference assessment to determine their nutritional status. Then, parents received personal counseling with a pediatrician to answer their questions and increase parental knowledge regarding the problem of malnutrition in children. In this social service, there were 10 children (37.0%) with undernutrition and three children (11.11%) with stunting. This social service received a positive response from the community and proved that education and sustainable child health services are still very much needed in Banjar Jagatamu, Meliling Village, Tabanan